Navigating the Digital Frontier: Challenges and Opportunities for Journalism in the Digital Age - Moehammad Iqbal Sultan; Andi Subhan Amir (International Journal of Educational and Life Sciences, 2023)
The digital age has brought about unprecedented changes in the field of journalism, reshaping the way news is produced, distributed, and consumed. This article explores the multifaceted challenges and opportunities that contemporary journalism faces in this digital landscape. Drawing upon a diverse set of academic references and industry insights, we examine the evolving role of journalists, the impact of social media, the rise of data journalism, and the need for media literacy in today's society. By understanding these dynamics, journalists and news organizations can better navigate the complexities of the digital frontier and continue to serve as reliable sources of information in an ever-changing media ecosystem.